2014
DOI: 10.1080/19440049.2013.865146
|View full text |Cite
|
Sign up to set email alerts
|

German database on the occurrence of food additives: application for intake estimation of five food colours for toddlers and children

Abstract: To get a more realistic estimation of food additive intake for toddlers and children, a German database on the occurrence of food additives was created. It uses consumption data of two recent national nutrition surveys for toddlers and children in combination with qualitative information of food additive occurrence in the consumed food. The information on food additive occurrence is based on food labelling. A categorisation system was developed according to regulations to classify the foods consumed and to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…Studies conducted in India (Rao et al 2004; Dixit et al 2011), Hong Kong (Lok et al 2010), Germany (Diouf et al 2014), Kuwait (Husain et al 2006; Sawaya et al 2008), Ireland (Connolly et al 2010) and Brazil (Toledo et al 1992) have focused on exposure to colour additives in children and/or adolescents. Finally, there have been studies in other countries that are specific for a certain colour additive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in India (Rao et al 2004; Dixit et al 2011), Hong Kong (Lok et al 2010), Germany (Diouf et al 2014), Kuwait (Husain et al 2006; Sawaya et al 2008), Ireland (Connolly et al 2010) and Brazil (Toledo et al 1992) have focused on exposure to colour additives in children and/or adolescents. Finally, there have been studies in other countries that are specific for a certain colour additive.…”
Section: Introductionmentioning
confidence: 99%
“…Verger et al (1998) have made the same conclusions. Diouf et al (2014) however have found a potential risk for annatto for children and toddlers with Tier 2 and for toddlers with the refined Tier 2 approach. Consequently further assessment of these additives for the Belgian adult population was found unnecessary, but should certainly be envisaged for youngsters.…”
Section: Tier 2 and Refined Tier 2 Exposure Assessmentmentioning
confidence: 93%
“…Risk assessment of food additives has been performed in several European Member States (Bemrah, Leblanc, & Volatier, 2008;Bemrah et al 2012;Connolly et al 2010;Diouf et al 2014;Leclercq, Molinaro, et al,2000;Mischek & Krapfenbauer-Cermak, 2012;Verger, Chambolle, Babayou, Le Breton, & Volatier, 1998;Vin et al, 2013). In Belgium specifically, exposure assessments of the population to benzoates, nitrates and nitrites, sulphites, lycopene, and artificial sweeteners have recently been performed (Bilau, Matthys, Vinkx, & De Henauw, 2008;Huvaere, Vandevijvere, Hasni, Vinkx, & Van Loco, 2012;Temme et al 2011;Vandevijvere et al 2009Vandevijvere et al , 2010Vandevijvere et al, 2014.)…”
Section: Introductionmentioning
confidence: 98%
“…A recent German study (Diouf et al, 2014) estimated Ponceau 4R (E 124) intake for toddlers (0.5 to <5 years old) and children (6-11 years old) according to two exposure scenarios. Results showed that the dietary exposure to the food additive was in the range of 0.3 mg/kg bw per day (mean) to 2.6 mg/kg bw per day (high level consumers) for toddlers, and in the range of 0.2 mg/kg bw per day (mean) to 2.3 mg/kg bw per day (high level consumers) for children (6-11 years old).…”
Section: Additional Informationmentioning
confidence: 99%